High speed target tracking radar system based on the use of BPSK signal and digital Doppler shift compensation - Golubičić, Zoran T.; Simić, Slobodan M.; Zejak, Aleksa J.; Reljić, Boro M.; Marić, Svetislav (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: This paper presents a model of a high speed target radar tracking system that is much simpler than the existing ones. The Doppler shift is compensated before signal compression, simultaneously with the modification of the clock signal in the compression filter. This is possible thanks to the development of FPGA technology. The most important for this application are very fast clock control units which enable operation with different frequency references up to 1 GHz with an accuracy far below 1 Hz. Methods: In this paper, the methodology of mathematical modeling and simulation is used. Results:The results of the analysis of the most important effects in radars caused by high-speed targets are presented and discussed - target migration through resolution cells and compression filter response distortion due to high target acceleration. Conclusion: Thanks to flexible RF and signal processing hardware, complex radar processing procedures are not required. The sensitivity of the BPSK signal to the Doppler shift (which is usually considered a disadvantage) can be used to reject targets at a slightly different rate. This system can be used in space debris tracking, airspace target tracking, car driving, etc.